Bank's Responsibility for Mistakes Made by Outsourced Workers - Djokdja, Galang Ramadhan; Laturette, Adonia Ivone; Angga, La Ode (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: In terms of national development, especially in the field of employment, Indonesia prioritizes achieving the greatest possible welfare for the working community. Every citizen has the right to obtain decent work as regulated in Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia as the Constitutional Basis of the Republic of Indonesia, which states.Purposes of the Research: The purpose of this study is to find out and analyze the banking party's responsibility for errors made by outsourcing workers. This study helps in seeing the procedures and Banking Responsibility for Errors Committed by Outsourced Workers.Methods of the Research: The research method used in this writing is normative research methods. Thus, this research collects data using library research, namely in the form of scientific materials such as legislation, books, official documents, publications and research results.Results Main Findings of the Research: Based on Article 29 of Financial Services Authority Regulations Number 1/POJK.07/2013 concerning consumer protection in the financial services sector, which states that financial service business actors or banks are obliged to be responsible for customer losses arising from errors and/or negligence of workers, both permanent workers and outsourced workers. financial service business actors and/or third parties working for the interests of financial service business actors. However, if the customer's loss arises from the customer's own error and/or negligence, the bank is not responsible for the loss.